Non–Femoroacetabular Impingement - Blankenbaker, Donna G.; Tuite, Michael J. (Seminars in Musculoskeletal Radiology, 2013)
Femoroacetabular impingement is one of the causes of hip pain leading to acetabular labral tears and cartilage damage that may lead to the development of early osteoarthritis. More recently other causes of impingement have been recognized that may be the culprit for the painful hip. These causes include ischiofemoral, anterior inferior iliac spine/subspine and iliopsoas impingement. Ischiofemoral impingement syndrome is related to narrowing between the ischial tuberosity and lesser trochanter with abnormalities of the quadratus femoris muscle producing hip pain. Anterior inferior iliac spine/subspine impingement syndrome is defined as hip pain produced by abnormal contact between the anterior inferior iliac spine and proximal femur. Iliopsoas impingement may produce hip pain that is related to a thickened or taut iliopsoas tendon at the level of the acetabular rim/anterior hip capsule. Radiographs, magnetic resonance imaging, ultrasound, or computed tomography may help to better elucidate the problem while excluding intra-articular pathology or femoroacetabular impingement. Keeping these causes of impingement in mind when evaluating the painful hip will aid in diagnosis.
Keywords: MR; CT; hip; Ischiofemoral impingement; subspine impingement; iliopsoas impingement